The Implementation of Problem-Based Learning as a Catalyst for Learning Autonomy among Students of the Sociology Education Study Program at Manado State University - Hamsah, Hamsah; Sidik, Ramdani (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
The paradigm shift in higher education toward student-centered learning requires pedagogical strategies that foster learner autonomy. In the context of the Sociology Education Study Program at Manado State University, the implementation of Problem Based Learning (PBL) represents an essential step to encourage students to take an active role in managing their own learning process. This study aims to analyze how PBL functions as a catalyst for students’ learning autonomy and to identify behavioral transformations that emerge during the process. The research employed a qualitative approach using a case study design. The participants consisted of ten students who had completed at least one semester of PBL-based courses, selected purposively based on their active engagement in the learning process. Data were collected through semi-structured in-depth interviews and direct classroom observations, then analyzed using thematic analysis techniques. The findings revealed four main themes: (1) the emergence of learning initiative, (2) the strengthening of reflective ability, (3) collaboration as a trigger for autonomy, and (4) initial challenges and adaptation to the new approach. These findings indicate that PBL not only enhances cognitive competence but also cultivates reflective awareness, academic responsibility, and self-confidence in managing the learning process. The implementation of PBL thus serves as a crucial catalyst in developing learning autonomy among sociology education students, provided that it is supported by lecturers’ facilitative roles, process-based evaluation systems, and a collaborative and reflective learning environment.